Levels and inhalation health risk of neonicotinoid insecticides in fine particulate matter (PM2.5) in urban and rural areas of China - Y. Zhou; Guo, J.; Z. Wang; B. Zhang; Sun, Z.; Yun, X.; J. Zhang (Environment International, 2020)
Neonicotinoid insecticide (NEO) concentrations in ambient fine particulate matter (PM2.5) and daily exposure via inhalation were investigated during spring and fall in an urban area in Beijing and in urban and rural areas of Zhengzhou, Henan Province, China. Four NEOs, including imidacloprid, acetamiprid, thiamethoxam and clothianidin, were assessed using a QuEChERS (quick, easy, cheap, effective, rugged, safe) extraction procedure coupled to liquid chromatography–tandem mass spectrometry. Of 64 PM2.5 samples, 100% contained at least two NEOs (imidacloprid and acetamiprid). Imidacloprid was detected at the highest levels, ranging from 4.33 to 1.13 × 102 pg m−3. A relative potency factor method that considered different toxicities was used to integrate the four NEO concentrations. The total NEO concentrations in air in the Zhengzhou rural area (mean: 80.86 pg m−3) were higher than those in urban areas. Differences between seasons were not significant (p > 0.05). The highest value for the total average daily dose via inhalation of four NEOs (ADDinh,total), 91.0 pg kg−1 day−1, was found in rural children <6 years old. The ADDinh,total of rural residents was significantly higher than that of urban residents when there was no intensive pesticide application. Although the ADDinh,total values were below the current chronic reference dose, when possible joint toxicity and the increasing use of NEOs are considered, a potential health risk via inhalation is evident. We believe this study is the first to characterize NEO levels in fine particulate matter and to evaluate inhalation exposure in urban and rural residents under nonoccupational scenarios in China. It will enhance our understanding of exposure to NEOs and provide a basis for risk management decisions. © 2020 The Author(s)
Keywords: acetamiprid; Adult; air pollutant; Air Pollutants; analysis; article; Beijing; Child; child health; China; clothianidin; concentration (composition); concentration (parameter); controlled study; environmental exposure; environmental impact assessment; extraction; Female; fine particulate matter; Fine particulate matter (PM2.5); health hazard; health risk; Health risks; Henan; human; Humans; imidacloprid; inhalation; insecticide; Insecticides; Liquid chromatography; Male; mass spectrometry; neonicotinoid; Neonicotinoid insecticides; neonicotinoid pesticide; Neonicotinoids; Particles (particulate matter); particulate matter; Pesticide applications; pollution exposure; Potential health risks; priority journal; respiration; Risk Assessment; Risk management; rural area; Rural areas; Seasonal variation; Tandem mass spectrometry; Thiamethoxam; Toxicity; Urban and rural areas; Urban and Rural Residents; urban area; Zhengzhou